'Chitosan in water' as an eco-friendly and efficient catalytic system for Knoevenagel condensation reaction. (15th December 2018) - Rani, Dhiraj; Singla, Priyanka; Agarwal, Jyoti
Graphical abstract: Highlights: Chitosan has been developed as an efficient, easily separable, reusable and heterogeneous organocatalyst for the Knoevenagel reaction. No side product formation was observed in any of the case studied resulting from the possible aldol reaction. DFT studies provided evidence for the high stability of intermediate generated by chitosan and aldehyde. Stereochemistry of E /Z isomers was analyzed by 2D-Noesy spectra. Abstract: The catalytic activity of commercially available chitosan has been investigated for the Knoevenagel reaction of ethylacetoacetate (EAA)/dimethylmalonate (DMM) with arylaldehydes. Among all the screened solvents, Chitosan performed the best in water as reaction medium. Substrate scope was evaluated by using various arylaldehydes and it was observed that presence of electron donating groups on aldehydes reduce the yields, while electron-withdrawing groups increase the yields. In case of the reaction of 4-bromobenzaldeyde with EAA, the lower yield of the corresponding product14 was obtained due to the high stability of imine intermediate formed and this postulate was proved by experiments as well as theoretical calculations. In case of EAA, the E/Z stereochemistry of the corresponding products was assigned based on NOESY experiment.